Características socio-familiares de los hogares de niños con discapacidad del Programa de Intervención Temprana PRITE-EE año 2018. - Roncalla Zumaeta, Nathaly Lizbet (2019)
The purpose of the thesis report is to know the family characteristics of households with children with disabilities of the PRITE EE early intervention program, that is, to highlight the family dynamics in terms of: its composition, structure, and knowledge of social characteristics such as: housing, health, religion and economics that will allow us to expand our knowledge of reality within each family. The families of children with disabilities were taken as a sample, using the methodology and techniques of quantitative and qualitative research, whose population is determined exactly by 43 families of the children of the PRITE EE. In chapter I; the problematic reality is raised using theories, approaches, and other studies carried out by different authors based on problems. In Chapter II; presents the methodology used for the compilation of statistical data from the sampling, application of the instrument is presented; and in addition, observation and interviewing techniques are supported. In chapter III; the presentation of results and discussion is made in relation to the research variable.